Use of weapons provided - Oprica, Oana-Alexandra (Eximia, 2023)
The topic presents the organization of the police institution, as well as its framing in the political realities of the interwar period. In order to achieve this objective, I have used a bibliographic material as extensive as possible, so that the result is as close as possible to scientific historical research. Following the analysis of human society, it should be specified that despite the modernization and improvement of the legislative system, the intensification of state intervention, justice and public safety, there is an increase in crime in all spheres, which implies the increasingly active presence of the police in places with a high degree of danger and mobilizing them to use the weapon provided when the situation requires it. Thus, in a society, man must respect the norms and principles for the smooth development of life, that is why norms and rules are indispensable in a society. My opinion is that, in the content of this paper, I have included all these aspects related to the policeman’s duties, the way to use weapons in borderline situations, the smooth running of activities and the successful fulfillment of all objectives, but last but not least, those situations in which the police officer inadvertently endangers his life or bodily integrity. Regardless of the missions in which they are to participate, a good policeman will adopt an impartial behavior towards everyone present at the scene and will avoid the use of the equipped weapon as much as possible. Thus, I consider it necessary for a policeman who carries out his activity in the interest of the citizen, to ensure his protection, to be well trained before using the weapon provided, in order to avoid possible injuries, or even the death of a person. I think that the weapon in the equipment is in most situations, the only way to mobilize particularly dangerous criminals, to avoid injury, endangering the policeman and other people present in the place.